2020
DOI: 10.1097/jnn.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Is a Catalyst for Future Changes in Stroke Nursing Care

Abstract: INTRODUCTION: During the COVID-19 pandemic, hospitals still have to meet external regulations while delivering compassionate patient care. This reflections article provides a solution for certified stroke programs to continue to meet stroke certification requirements. One area of focus, in this article, is stroke education. Because of “shelter-in-place orders,” there were no visitors permitted at the bedside, yet we know that high-quality poststroke education is important to improve outcomes. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…5 Nursing ingenuity and nursing innovations were propelled during the COVID-19 pandemic and continue to expand as the pandemic lingers. 6,7 The successful transition of this TBI support group to a virtual format allowed the facilitators to continue to provide community resources and social support to…”
Section: Implications For Nursesmentioning
confidence: 99%
“…5 Nursing ingenuity and nursing innovations were propelled during the COVID-19 pandemic and continue to expand as the pandemic lingers. 6,7 The successful transition of this TBI support group to a virtual format allowed the facilitators to continue to provide community resources and social support to…”
Section: Implications For Nursesmentioning
confidence: 99%
“…Nurses working in stroke centers and other settings have come up with creative solutions to help minimize the use of scarce personal protective gear (eg, 3D printers), maintaining open lines of communication with staff and leadership, providing remote family poststroke education, and continuing effective staff collaboration (eg, Adapted Stroke Unit Model) while following COVID-19 guidelines. 2–4 Wira et al 5 offers suggestions on how stroke center nurses, nurse practitioners, and physician associates could be reassigned to provide more direct patient care (eg, ER, floor, ICU) during the pandemic and placed on teams following additional education and mentorship. Finally, Liaw et al 6 describe how the COVID-19 pandemic resulted in the development of best practice recommendations for stereotactic radiosurgery for stroke patients illustrating how a crisis can lead to positive outcomes (eg, guidelines).…”
Section: Acute Carementioning
confidence: 99%
“…19 During the pandemic successful application has been described in TIA clinics, 35 physical, occupational, and speech therapy rehabilitation, 36 and nursing communication with families. 37 The benefits of video technology, allowing limited examination and an awareness of the patient’s expression, over telephone consultation have been demonstrated. 38 It was often suggested that many stroke patients, being elderly, would not manage well with the technology but video technology has been shown to be well adopted to by outpatients with stroke and cognitive impairment.…”
Section: Telemedicine In Clinical Stroke Care and Research—a Possiblementioning
confidence: 99%